Impact of environmental temperatures on resistance to organophosphate insecticides in Aedes aegypti from Trinidad Repercusión de las temperaturas ambientales sobre la resistencia de Aedes aegypti a los insecticidas organofosforados en Trinidad - Karen A. Polson; William G. Brogdon; Samuel C. Rawlins; Dave D. Chadee (Pan American Health Organization, 2012)
OBJECTIVE: To examine the effects of increasing larval rearing temperatures on the resistance status of Trinidadian populations of Aedes aegypti to organophosphate (OP) insecticides. METHODS: In 2007-2008, bioassays and biochemical assays were conducted on A. aegypti larvae collected in 2006 from eight geographically distinct areas in Trinidad (Trinidad and Tobago). Larval populations were reared at four temperatures (28 ± 2ºC, 32ºC, 34ºC, and 36ºC) prior to bioassays with OP insecticides (fenthion, malathion, and temephos) and biochemical assays for esterase enzymes. RESULTS: Most larval populations reared at 28 ± 2ºC were susceptible to fenthion (>98% mortality) but resistant to malathion and temephos (< 80% mortality). A positive association was found between resistance to OP insecticides and increased activities of α- and β-esterases in larval populations reared at 28 ± 2ºC. Although larval populations reared at higher temperatures showed variations in resistance to OPs, there was a general increase in susceptibility. However, increases or decreases in activity levels of enzymes did not always correspond with an increase or decrease in the proportion of resistant individuals reared at higher temperatures. CONCLUSIONS: Although global warming may cause an increase in dengue transmission, based on the current results, the use of insecticides for dengue prevention and control may yet be effective if temperatures increase as projected. OBJETIVO: Examinar los efectos del aumento de las temperaturas de desarrollo larvario sobre el estado de resistencia a los insecticidas organofosforados de las poblaciones de Aedes aegypti en Trinidad. MÉTODOS: En 2007 y 2008 se llevaron a cabo ensayos biológicos y bioquímicos en larvas de A. aegypti recogidas en el 2006 de ocho áreas geográficamente separadas en Trinidad (Trinidad y Tabago). Las poblaciones larvarias se desarrollaron en cuatro temperaturas (28 ± 2 ºC, 32 ºC, 34 ºC y 36 ºC) antes de los ensayos biológicos con insecticidas organofosforados (fentión, malatión ...